Analysis for Science Librarians of the 2018 Nobel Prize in Physics: Using Light as a Tool for New Discoveries. Issue 1 (2nd January 2019) - Bohémier, Kayleigh Ayn
ABSTRACT: The 2018 Nobel Prize in Physics went to Arthur Ashkin, Donna Strickland, and Gérard Mourou for important advances in how lasers are used. Ashkin is the pioneer behind radiation pressure-induced optical levitation and trapping, an important technique in physics, chemistry, and biology. Strickland and Mourou invented chirped pulse amplification, which has led to a revolution in how high-energy pulsed lasers can be used everywhere from the laboratory to the hospital. This paper describes the science behind the prize and provides biographical profiles for the new laureates, most notably a citation analysis using Web of Science, Scopus data, and network graph tools.